The correlation between the intake of coffee and the prevalence of asthma: a dose response meta-analysis and Mendelian randomization study - Deqing Miao; Xiaojie Yuan; Yujia Chen; Xiaogang Yu; Zhe Liu; Fan Zhou; Wen Li; Qian Li; Zhiliang Fan; Yihui Chai (Food & Nutrition Research)
Objectives: Asthma contributes to a significant global disease burden. Coffee has been linked to a reduced risk of asthma in several epidemiological studies. However, conflicting findings create confusion regarding the role of coffee in asthma management. We executed a consolidated analysis in conjunction with a Mendelian randomization (MR) study with the aim of scrutinizing the potential correlation between coffee intake and the susceptibility to asthma development. Furthermore, we analyzed the dose-response relationship between coffee intake and the onset of asthma. Methods: In this meta-analysis, we searched online to identify studies involving coffee consumption on the risk of asthma. The primary outcome was the risk of asthma development. We used RevMan and R language to calculate the pooled results and create plots. A meta-package dosresmeta was used for dose-response analysis. In the MR analyses, we obtained data from public databases. MR studies were conducted using genome-wide association data for coffee intake. Independent genetic instrumental variants strongly associated with each exposure (P < 5*10^-8) were considered as instruments. The inverse variance-weighted method was used in the primary analysis. Sensitivity analyses were also conducted. Results: We ultimately incorporated four publications into our meta-analysis. Our study encompassed 671,417 participants and elucidated a negative correlation between the intake of ground coffee and the incidence of asthma (pooled odds ratios [OR] = 0.86, 95% confidence interval [CI] = 0.82–0.91, I2 = 66.2%). A potential nonlinear relationship between coffee and asthma was discovered. A J-shaped dose-response association was found between ground coffee consumption and the risk of asthma development, with the lowest risk of asthma occurring at approximately 2–3 cups per day. In the MR study, the findings suggest a decrease in asthma risk associated with ground coffee consumption (OR = 0.982, 95% CI 0.972–0.992; P = 0.000). Sensitivity analyses revealed that the causality estimations were robust. Conclusion: A comprehensive analysis of epidemiological studies and an MR analysis indicate a correlation between coffee intake and a decreased risk of asthma. Furthermore, dose-response analysis of observational studies reveals that consuming an optimal amount of 2–3 cups of coffee every day is associated with the lowest risk of asthma, as opposed to abstaining from coffee or consuming more than four cups daily.